(untitled) (Fiep Bulletin - online, 2014)
This study is part of a research matrix and has the objective of verifying the provision of physical education (PE) in public schools in the cities of Maceio, Arapiraca , Palmeira dos Índios, Anadia, União dos Palmares, Teotônio Vilela, Marechal Deodoro, Rio Largo and São Miguel dos Campos to contribute to a diagnosis of the situation in relation to the educational curriculum component PE in the state of Alagoas . Constitutes a form of field research, exploratory, descriptive and transversal, which established visits in different microregions of Alagoas. Until the last step was visited 248 schools where we find the lack of PE teachers and still not offer the curricular component PE among other scholarly knowledge . All municipalities involved show that the biggest problem related to everyday school life is directly linked to physical space and materials available for PE classes. The Sport is the main content and participation in class, the main criterion for evaluation of PE. Teachers conduct planning for their classes and are based on assumptions of social and health aimed at the PE school. Was also verified the presence of people with disabilities performing practical experiences in PE classes.